Hypothalamic tumor associated with atypical forms of anorexia nervosa and diencephalic syndrome - Eugenio Chipkevitch; Antonio C.L. Fernandes (Arquivos de Neuro-Psiquiatria)
We report the case of a 10-year-old girl with a mature teratoma in the hypothalamic region. The patient presented a 2-month history of anorexia, psychic disturbances and a 37% loss of body weight. These symptoms had led initially to a diagnosis of major depression and atypical anorexia nervosa. She also presented some signs and symptoms of diencephalic syndrome. This case illustrates the importance of considering a slow-growing mass as a rare but real possibility in the differential diagnosis of anorexia nervosa, mainly in atypical cases.